Analysis On Factors Influencing Career Womens Fear Of Success And Its Effect On Work Performance (A Study In Semarang City) - Triyani, Dian; Surjanti, Rr. Lulus Prapti N.S. (Universitas Semarang, 2017)
Fear of success occurs when a person receives a distraction in the form of fear of his own ability to complete or attempt to complete a challenging task or job. This study aims to conduct an empirical test and analyze the effect of social support, career development and work competition situation against fear of success, and its effect on work performance. The total number of samples in the study is 96 respondents, with a specific characteristic of married women working in banking.The study employs SPSS for analysis technique. The results show that social support affects negatively fear of success, thus the higher the social support, the less the fear of success. On the other hand, factors of career development and work competition situation affect positively fear of success. Thus, the higher career development and job competition, the greater the fear of success. Further, fear of success factor affects positively on the career performance of career women. A person who has fear of successful career, in which she attributes the success internally, then she is at her high performance.